The Role of Teachers and Digital Literacy Competencies - Dwi Kartikawati; Nurhasanah Nurhasanah (Pelopor Publikasi Akademika, 2024)
This research focuses on how the Role of Teachers in Improving Digital Literacy Competencies in the Digitalization Era. In the rapid development of technology, teachers must have a strong understanding of technology and how to use it effectively in the learning process. They must be familiar with the latest technological devices and applications that can enhance their learning. Teachers must also be able to teach students about digital skills and information literacy, including the ability to access, eval_uate, and use information critically. Teachers play a role in 10 roles, including as facilitators, and managers of technology-based learning. They must have a deep understanding of relevant technologies and be able to integrate them into the learning process. By departing from qualitative methods, later this research can answer the Role of Teachers in Improving Digital Literacy Skills in Facing the Challenges of Change in the Digitalization Era.